Composição do gasto público e crescimento econômico: uma avaliação macroeconômica da qualidade dos gastos dos Estados brasileiros (Economia Aplicada, 2007)
The purpose of this paper is to determine which components of public expenditure explained the Brazilian states´economic growth during the period 1986-2003. Expenditures are decomposed according to their economic classification (current and capital expenditures), and also according to their functional classification (transportation and communication, education, defense and health). Capital expenditures seem to be productive, that is, they enhance economic growth, while current expenditures are productive only if they represent less than 61% of total expenditure. Expenditures on transportation and communication, education, and defense also contribute to economic growth.